IMPLEMENTASI FUNGSI KEPEMIMPINAN KEPALA SEKOLAH DI SD INPRES ARMOPA IV BONGGO KABUPATEN SARMI - ROMANSA SISO (NOKEN : Jurnal Pengelolaan Pendidikan, 2020)
The aim of the study was to describe the implementation of school principal leadership in decision making, instruction, consultation, participation, and delegates’ roles. This study used descriptive qualitative method with a case study approach. The data source were from the school principal, teachers, school committee and supervisors. The data collection techniques were in-depth interviews, participatory observation, and documentation. The data validation technique was using extension of involvement, the persistent of observation, triangulation and peer reviews. The result of the research showed that the school principal of the Armopa IV Elementary School on Bonggo has implemented the 5 leadership roles which were (1) the principal in making decision involved the teachers and school committee, considering public interests, dare to make decisions on all the consequences, wise and open. (2) Instruction role showed that the principal mandates the teachers to have learning preparations such as Rencana Pelaksanaan Pembelajaran (RPP). (3) The consultation role was implemented through consultation on writing activities and program reports as well as being supportive and provide consultations for teachers. (4) Participation roles was implemented through the principal being a good role model and active in participating to all school activities. (5) Delegate roles was implemented through building up trust on teachers and staff to also get involve in outside school meetings, leading meeting and leader of Monday ceremonies. Key Words:  Leadership Roles, School Principal, Elementary School